Large magnetic field effects in electrochemically doped organic light-emitting diodes - Reenen, Stephan van; Kersten, S. P.; Wouters, S. H. W.; Cox, Mark G. D. M.; Janssen, Paul; Koopmans, Bert; Bobbert, Peter A.; Kemerink, Martijn (Physical review. B, Condensed matter and materials physics, 2013)
Large negative magnetoconductance (MC) of ∼12% is observed in electrochemically doped polymer light-emitting diodes at sub-band-gap bias voltages (Vbias). Simultaneously, a positive magnetoefficiency (Mη) of 9% is observed at Vbias = 2 V. At higher bias voltages, both the MC and Mη diminish while a negative magnetoelectroluminescence (MEL) appears. The negative MEL effect is rationalized by triplet-triplet annihilation that leads to delayed fluorescence, whereas the positive Mη effect is related to competition between spin mixing and exciton formation leading to an enhanced singlet:triplet ratio at nonzero magnetic field. The resultant reduction in triplet exciton density is argued to reduce detrapping of polarons in the recombination zone at low-bias voltages, explaining the observed negative MC. Regarding organic magnetoresistance, this study provides experimental data to verify existing models describing magnetic field effects in organic semiconductors, which contribute to better understanding hereof. Furthermore, we present indications of strong magnetic field effects related to interactions between trapped carriers and excitons, which specifically can be studied in electrochemically doped organic light-emitting diodes (OLEDs). Regarding light-emitting electrochemical cells (LECs), this work shows that delayed fluorescence from triplet-triplet annihilation substantially contributes to the electroluminescence and the device efficiency.